Fifth Seminar on the Middle East - Pedro Brieger (International Institute of Islamic Thought, 2005)
Studies of the Middle East and the Islamic world have developed considerably in Argentina over the last 10 years because, among other reasons, this country was targeted twice by terrorists who still remain unknown: The Embassy of Israel was bombed in 1992, and the central headquarters of the Jewish community (AMIA) was bombed in 1994. Given that even today we do not know who carried out these attacks and why, the topic of the Middle East has acquired a public dimension that it did not have before. In fact, these actions led to the creation of university study centers and chairs dedicated to the study of the Arab and Islamic worlds.1 However, their academic output is still in the initial stage. On 10-11 November 2004, the Fifth Seminar on the Middle East conference took place at the Universidad Nacional de La Plata (UNLP), in La Plata, Argentina. The Department of the Middle East of the UNLP’s Institute of International Relations organizes this conference every 2 years, since it is one of the few universities that has a specific department dedicated to Middle Eastern studies. Moreover, it is the only one that has, since 1997, consistently managed to bring Argentine academics together to share ideas and discuss the contemporary reality of the Middle East and the Islamic world. During this conference, articles were presented on a wide range of themes, always searching for the best way to link together the most relevant events of contemporary reality. For this reason, in 2002 the focus was on the implications of the 9/11 tragedy. The current conference concentrated on the war in Iraq, a logical continuation of the discussion in 2002. Professors from 14 Argentine universities, as well as from Spain, the United States, and Mexico, participated in the panels. The first panel analyzed Islamic thinking and practice after 9/11. Augustín Galli (University of Buenos Aires [UBA], Argentina) laid out the evolution of Islamic movements in Algeria. Damián Setton (UBA), who is investigating the various ...